COMPARISON OF TWO TECHNIQUES FOR EVALUATING SPHERICAL INDENTATION DATA - Aleš Materna; Petr Haušild; Jan Ondráček (Acta Polytechnica CTU Proceedings)
Flow curves of 15Kh2MFA, Sv 08Kh19N10G2B and 08Kh18N10T steels used for fabrication of WWER-440 nuclear reactor pressure vessel and core internals were obtained using the automated ball indentation (ABI) test technique and compared with flow curves evaluated from the same measured load-displacement data and widely used Oliver-Pharr method. Differences in results obtained by both studied methods do not exceed 12 % and are attributed to the amount of material pile-up.